Studi Kewirausahaan dalam Pariwisata Olahraga: Analisis Bibliometrik - Ni Putu Erna Surim Virnayanthi; I Made Candiasa; I Gede Ratnaya; Ni Ketut Widiartini; Desak Putu Parmiti (Postgraduate, University of Mataram, 2024)
Bibliometric analysis provides valuable insights into developing entrepreneurial aspects in sports tourism. This study explores key research trends and themes in the intersection of sports tourism and entrepreneurship. The analysis of 200 articles using the keyword